Lama Permainan Game Online Terhadap Gangguan Pola Tidur Mahasiswa - Fitria, Reni (Universitas Fort De Kock Bukittinggi, 2019)
The development of technology in this area is very rapid, various technological advances such as playing online games can be obtained easily. The long time playing online games is expected to affect the disruption of sleep patterns of male Dharmas University male dormitory students. The purpose of this study was to find out the relationship between the duration of online game games to the disturbance of sleep patterns of male students at Dharmas University in Indonesia. The method used is descriptive analytic with cross sectional research design. This research was conducted in the male dormitory of Dharmas Indonesia University with a sample of 42 students. The sampling technique is total sampling. Bivariate analysis uses the chi square test. The results of the study were 42 respondents, almost all 32 (76.2) who played online games excessively in the male dormitory of Dharmas Indonesia University. Most of them got 22 (52.4) students experiencing sleep patterns. Based on the old chi-square statistical test online game play on sleep patterns disturbances in getting the value (p value = 0.022) this study shows that there is a long relationship between online game play and sleep disorders. It is hoped that students will reduce the duration of playing online games, sleep at 9:00 p.m. / 10:00 p.m., and the board administrators will control the dorms more. Keywords: Online games, sleep patterns